Ответ:
R⊂⊂ ![(-1\frac{1}{3} ;-1) (-1\frac{1}{3} ;-1)](https://tex.z-dn.net/?f=%28-1%5Cfrac%7B1%7D%7B3%7D%20%3B-1%29)
Пошаговое объяснение:
больше ![x+2 x+2](https://tex.z-dn.net/?f=x%2B2)
Возведем все в куб, чтобы избавиться от корня;
(x+2)^{3} \\\\x^{3} -2x>x^{3} +6x^{2} +12x+8\\x^{3} -2x-x^{3} -6x^{2} -12x-8>0\\-6x^{2} -14x-8>0\\" alt="x^{3} -2x>(x+2)^{3} \\\\x^{3} -2x>x^{3} +6x^{2} +12x+8\\x^{3} -2x-x^{3} -6x^{2} -12x-8>0\\-6x^{2} -14x-8>0\\" align="absmiddle" class="latex-formula">
Домножим на -1;
0\\6x^{2} +14x+8=0" alt="6x^{2} +14x+8>0\\6x^{2} +14x+8=0" align="absmiddle" class="latex-formula">
D=196-192=4
![\sqrt{4} =2 \sqrt{4} =2](https://tex.z-dn.net/?f=%5Csqrt%7B4%7D%20%3D2)
![x1=\frac{-14+2}{12} =-1 x1=\frac{-14+2}{12} =-1](https://tex.z-dn.net/?f=x1%3D%5Cfrac%7B-14%2B2%7D%7B12%7D%20%3D-1)
![x2=\frac{-14-2}{12} =\frac{-16}{12} =\frac{-4}{3} =-1\frac{1}{3} x2=\frac{-14-2}{12} =\frac{-16}{12} =\frac{-4}{3} =-1\frac{1}{3}](https://tex.z-dn.net/?f=x2%3D%5Cfrac%7B-14-2%7D%7B12%7D%20%3D%5Cfrac%7B-16%7D%7B12%7D%20%3D%5Cfrac%7B-4%7D%7B3%7D%20%3D-1%5Cfrac%7B1%7D%7B3%7D)
0 \\x>-1" alt="(x+1)(x+1\frac{1}{3} )<0\\x+1>0 \\x>-1" align="absmiddle" class="latex-formula">
ИЛИ
![x+1\frac{1}{3} <0\\x<-1\frac{1}{3} x+1\frac{1}{3} <0\\x<-1\frac{1}{3}](https://tex.z-dn.net/?f=x%2B1%5Cfrac%7B1%7D%7B3%7D%20%3C0%5C%5Cx%3C-1%5Cfrac%7B1%7D%7B3%7D)
Получаем:
![-1\frac{1}{3} <x<-1\\\\ -1\frac{1}{3} <x<-1\\\\](https://tex.z-dn.net/?f=-1%5Cfrac%7B1%7D%7B3%7D%20%3Cx%3C-1%5C%5C%5C%5C)